2004
DOI: 10.1115/1.1940667
|View full text |Cite
|
Sign up to set email alerts
|

Strength Analyses of Sandwich Pipes for Ultra Deepwaters

Abstract: Design requirements for pipelines regarding both ultimate strength and flow assurance in ultra deepwater scenarios motivated the development of a new sandwich pipe which is able to combine high structural and thermal insulation properties. In this concept, the annulus is filled with low cost materials with adequate thermal insulation properties and good mechanical resistance. The aim of this research work is to perform small-scale laboratorial tests and to develop a finite element model to evaluate the structu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(19 citation statements)
references
References 14 publications
0
19
0
Order By: Relevance
“…Substituting Eqs. (13)- (15) into (12), the propagation pressure, P p2 , of the PIP system is obtained as:…”
Section: Analytical Solution Of Propagation Pressure Of Pipe-in-pipe mentioning
confidence: 99%
See 1 more Smart Citation
“…Substituting Eqs. (13)- (15) into (12), the propagation pressure, P p2 , of the PIP system is obtained as:…”
Section: Analytical Solution Of Propagation Pressure Of Pipe-in-pipe mentioning
confidence: 99%
“…The work done by Xue et al [9] investigates the effect of corrosion in the propagation buckling of subsea pipelines. Buckle arrestors [1,18], pipe-in-pipe system [10][11][12][13][14], sandwich pipe system [15] and ring-stiffened pipelines [16], are used to confine the propagation buckling in subsea pipelines.…”
Section: Propagation Buckling Of Single Pipe 11 Introductionmentioning
confidence: 99%
“…The model employed in this work is similar to those from Estefen et al (2005), which were validated with small-scale experimental tests. The collapse curvature corresponds to the maximum moment reaction at the reference node.…”
Section: Numerical Model For Combined Loadingmentioning
confidence: 99%
“…The objective of this type of pipe is to increase the thermal insulation capacity to prevent blockage of the line caused by dropping fluid temperature below that required to form paraffin or hydrate. Numerical and experimental studies carried out by Estefen et al (2005) for the ultimate strength under combined external pressure and bending indicated that SP is viable for application in water depths up to 3,000 meters. In the case of SP, object of this study, the annular layer characteristics differ from PIP by satisfying simultaneously mechanical and thermal requirements.…”
Section: Introductionmentioning
confidence: 99%
“…Sato and Patel [2007] and Sato et al [2008] studied the buckling behavior of a PIP system under hydrostatic pressure and developed a simplified solution for estimating a PIP system's buckling capacity. Castello and Estefen [2006; and Estefen et al [2005] studied the feasibility of a sandwich pipe system for deep water applications with both numerical and experimental approaches. In another study, Castello and Estefen [2007] investigated the ultimate strength of sandwich pipes under combined external pressure and bending for several degrees of adhesion between the core layer and outer pipe.…”
Section: Introductionmentioning
confidence: 99%